Real-World Experience of Immunotherapy from India in Recurrent Squamous Cell Carcinoma of Head and Neck Cancer - Abbas, Waseem; Gupta, Saurabh; Goel, Vineeta; Rao, Ranga R.; Pankaj, Promila; Tripathi, Devashish; Patil, Pratik P.; Popli, Swati (South Asian Journal of Cancer, 2021)
Background Recurrent metastatic head and neck squamous cell carcinoma (HNSCC) patients carry a poor prognosis and have limited therapeutic options. In the randomized phase-3 trial CheckMate 141, nivolumab showed benefit in overall survival (OS) with manageable toxicity. Nivolumab is available for clinical practice since 2017 in India. The aim of this study is to evaluate the efficacy and safety of nivolumab in real-world settings in India.Materials and Methods This is a retrospective, single-center study on the use of nivolumab with advanced or metastatic HNSCC in India. Eligible patients had histologically confirmed, recurrent squamous cell carcinoma of the head and neck (including metastatic disease) of the oral cavity, pharynx, or larynx that was not amenable to curative treatment, tumor progression, or recurrence after the administration of platinum-containing chemotherapy administered as adjuvant therapy or in the context of primary or recurrent disease. We assessed demographics, safety (the Common Terminology Criteria for Adverse Events Version 4.0), response evaluation (the Response Evaluation Criteria in Solid Tumors Version 1.1), progression-free survival (PFS), and OS.Results Among patients with platinum-refractory, recurrent HNSCC, and treatment with nivolumab resulted in median PFS of 2 months and median OS of 5 months, which is inferior to what was seen in CheckMate 141. Fifteen of 20 patients (75%) had progressive disease, 3 (15%) showed a partial response, and 2 (10%) had stable disease.Conclusion Nivolumab was well tolerated in our study with fewer toxic effects, and an inferior median survival was reached as compared with CheckMate 141 in platinum refractory, recurrent HNSCC patients treated with nivolumab because 90% of patients in our study received nivolumab as second-line therapy after progression. Our study encourages the use of nivolumab in this population.
Keywords: immunotherapy in head and neck cancers; immunotherapy in India; immunotherapy in recurrent head and neck cancers; treatment of cisplatin refractory head and neck cancers; treatment of recurrent head and neck cancers